Health Problems that Hinder Student Learning in Chiangrai Pilot Schools: Mixed Methods Research - Sriklaub, Kanit; Tippayakulpairoj, Darunee; Amornpaisarnloet, Watinee; Srisuttiyakorn, Siwachoat; Jaengaksorn, Nattapol; Waleeittipat, Sakulkarn; Imsombat, Aree (Journal of Research Methodology, 2023)
This research aimed to analyze health problems and their causes that hinder student learning in Chiangrai pilot schools. In this 2-phase research, the analysis of health problems of student learning was collected by focus groups of principals and teachers of Chiangrai pilot schools. Focus group data were analyzed using content analysis to develop a questionnaire. The questionnaire was validated using content validity. Data from students were collected through class teachers and were analyzed by using descriptive statistics and grouping students according to health problems. In the second phase, the analysis of health problem causes was conducted by in-depth interview via Zoom video conference. Data from principals and teachers were collected through semi-structured interviews and analyzed using content analysis. The key findings were as follows: Health problems that hindered student learning in 11 schools were vision, hearing, oral, skin, digestive tract, malnutrition, movement, and hygiene problems. Characteristics of physical health problems according to the grade level were as follows: students from kindergarten to early elementary school had toothache, lice, and skin rash problems. The upper elementary and secondary students had body odor, skin rash, and malnutrition problems. Causes of health problems were divided according to the nature of the problem as follows: 1) the causes of students’ hygiene problems found that the students lacked knowledge of proper hygiene and the students did not aware of health problems effects due to culture, family tradition, and poverty, and 2) the causes of malnutrition problem in secondary students caused by culture, family traditions, and poverty.